2013
DOI: 10.1039/c3nr02031b
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin graphitic carbon nitride nanosheets: a low-cost, green, and highly efficient electrocatalyst toward the reduction of hydrogen peroxide and its glucose biosensing application

Abstract: In this communication, we demonstrate for the first time that ultrathin graphitic carbon nitride (g-C₃N₄) nanosheets can serve as a low-cost, green, and highly efficient electrocatalyst toward the reduction of hydrogen peroxide. We further demonstrate its application for electrochemical glucose biosensing in both buffer solution and human serum medium with a detection limit of 11 μM and 45 μM, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
175
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 332 publications
(180 citation statements)
references
References 32 publications
5
175
0
Order By: Relevance
“…Consequently, the development of artificial enzymes has very rapidly emerged as a lively field of research. Up to now, a variety of nanomaterials, such as metal oxide-based nanomaterials [4][5][6][7], graphene oxide (GO) [8,9], carbon nanotubes [10][11][12], carbon nanodots [13][14][15][16], carbon nitride sheets [17,18] and dots [19], graphene quantum dots (GQDs) [20][21][22], noble metal-based nanomaterials [23][24][25] and so on, are shown to possess unique intrinsic peroxidase-like catalytic activities. These nanomaterials are suitable for bioanalysis owing to their small size, excellent stability, and biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the development of artificial enzymes has very rapidly emerged as a lively field of research. Up to now, a variety of nanomaterials, such as metal oxide-based nanomaterials [4][5][6][7], graphene oxide (GO) [8,9], carbon nanotubes [10][11][12], carbon nanodots [13][14][15][16], carbon nitride sheets [17,18] and dots [19], graphene quantum dots (GQDs) [20][21][22], noble metal-based nanomaterials [23][24][25] and so on, are shown to possess unique intrinsic peroxidase-like catalytic activities. These nanomaterials are suitable for bioanalysis owing to their small size, excellent stability, and biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the Qin group has recently demonstrated that platinum nanoparticles were much more active and stable toward the catalytic decomposition of hydrogen peroxide (H 2 O 2 ) than catalase (one kind of bio-enzyme), and then a novel portable immunoassay method was developed by using platinum nanoparticles as a signal-transduction label with a detection limit of 0.5 ng mL À 1 cytokeratin-19-fragments (Song et al, 2014). Generally, the catalytic performance of nanocatalysts can be further enhanced by controlling their size, shape, composition, and surface structure (Guo et al, 2013;Huang et al, 2011;Tian et al, 2007Tian et al, , 2013aTian et al, , 2013b. Recent reports have shown that platinum-based bimetallic nanocatalysts, typically gold@platinum nanohybrids, were more active for a variety of electrochemical reactions (e.g., oxygen reduction reaction and formic acid oxidation reaction) when compared to monometallic platinum, owing to the change in the electronic structure and surface atomic arrangement (Hong et al, 2012;Kim et al, 2010;Lim et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was reported that g-C 3 N 4 could promote the hydrogen generation by water splitting under visible light illumination, which inspired researchers to further explore modification of g-C 3 N 4 structures with enhanced photocatalytic performance [12]. An efficient strategy is to exfoliate g-C 3 N 4 in bulk form to corresponding nanosheets by means of diverse methods [13][14][15][16]. During exfoliation, multilayer structure is destroyed to create numerous thin sliced fragments with enlarged specific surface area exposed.…”
Section: Introductionmentioning
confidence: 99%